, It’s not easy in the hut, ma’am”. The daily life of the Vlach shepherds in the huts on the borderland between Poland and Slovakia in the 21st century as the cultural heritage of the Carpathian region (selected issues) - Kocój, Ewa Maria (Balcanica Posnaniensia. Acta et studia, 2019)
The purpose of this article is to present the preliminary results of the research on the shepherds' everyday life that I have been conducting since 2015 in the field of history, migration, and cultural heritage of the Vlach minority inhabiting the areas from Albania to the northern Carpathians. One of the research stages entails the studies of the daily life and rituals of the highlanders living in the huts on the Polish side of the Carpathians. The article describes the issues concerning the organization and the time-space symbolism of a modern hut, including their daily life and schedule of activities. The research was conducted in the selected huts of Spiš, Orava, Podhale, Żywiec region, and Silesian Beskids in Poland in 2015-2018. In all cases, I applied qualitative research, mostly structured and unstructured interviews with senior and young shepherds working in the huts, as well as covert and overt participant observations conducted during selected pastoral holidays and meetings in various spaces—in temples, during highlander's and Vlach conventions, in theme meetings, and in the huts. I supplement these techniques with the analysis of the visual sources that I made during the field research, received from the enthusiasts of this topic, or found on the Internet. The research has shown that modern pastoralism oscillates between two poles: the traditional, which has made it possible to retain many elements from the past (cultural heritage), and the modern, thanks to which shepherds introduce global solutions to their huts and traditions.